KARAKTERISTIK PEMBUNGAAN DAN SISTEM PERKAWINAN NYAMPLUNG (Calophyllum inophyllum) PADA HUTAN TANAMAN DI WATUSIPAT, GUNUNG KIDUL - ILG Nurtjahjaningsih; Purnamila Sulistyawati; AYPBC Widyatmoko; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2012)
Flowering are influenced by internal factors, such as genetic and phytohormone, and environment factors, such as sunlight and nutrition intake. The flowering characteristics influence fruiting and genetic diversity seedlings through mating systems. This study aims to assess flowering and fruiting characteristics and to determine pattern of mating system of a Calophyllum inophyllum plantation at Watusipat, Gunung Kidul. Flowering and fruiting were observed at 4 locations, 3 parts of crown, and 4 main directions to know the effects of sunlight, nutrition intake and phytohormone in the flowering process. Mating system was assessed by comparing genetic diversity values between parent trees and offsprings. The values of genetic diversity were analyzed using 5 RAPD primers with 17 polymorphic loci. Analysis of variant showed that the locations, crown parts, directions and interaction between a location and direction significantly affected to differences number of flowers and fruits. Values of genetic diversity (h) of parent trees ranged between 0.1471 and 0.3056. The values increased at almost overall offsprings; it ranged between 0.2864 and 0.3750. Values of genetic distance (Da) between parent trees were high and very high (0.197 – 0.364), but the values was decreased between parent trees and their offspring, even between offspring populations. A dendrogram showed two main clusters; first cluster consisted parent trees at up edge with rare trees and second cluster consisted sub cluster parent trees at up edge; sub cluster parent trees at down middle; and sub cluster parent trees at down edge and overall offsprings. Flowering/ fruiting characteristics and pattern of mating systems of C. inophyllum were briefly discussed. Key words : Flowering characteristic, genetic diversity, Calophyllum inophyllum, RAPD analysis